Islamic School Financial Management: A Case Study of Islamic Junior High Schools in Rural Areas - Evi Erfiyana; Opan Arifudin; Ika Kartika (Yayasan Azka Hafidz Maulana, 2025)
This study aims to understand and explore financial management in rural Islamic junior high schools (Madrasah Tsanawiyah) from the perspective of Islamic school management. The method used was a qualitative case study approach, allowing researchers to gain an in-depth understanding of the financial management process, challenges, and strategies implemented by the madrasahs. Data were collected through interviews, observations, and documentation from madrasah administrators and teachers. The results indicate that financial management in these madrasahs remains traditional and relies on community funding and voluntary donations. The main obstacles faced are limited resources and a low understanding of professional financial management. Nevertheless, some madrasahs have begun implementing more transparent and accountable financial management systems to improve operational sustainability. These findings provide an important contribution to the development of Islamic-based madrasah financial management in rural areas and provide input for efforts to improve the professionalism of Islamic school financial management.